Store Atmosphere's Impact on Noodle Consumers' Purchasing Decisions: Pengaruh Suasana Toko terhadap Keputusan Pembelian: Wawasan dari Konsumen Mie - Rini Ayu Agustin; Dewi Komala Sari (Academia Open, 2023)
This research aims to examine the impact of store atmosphere, food quality, and service quality on purchasing decisions within the context of the Noodle Kingdom in Sidoarjo. Employing a quantitative approach, data were collected from 100 customers who had purchased products from the Noodle Kingdom. The analysis employed multiple linear regression using the SPSS version 25 software. The findings of this study demonstrate that store atmosphere significantly influences perceived quality and subsequently affects purchasing decisions. These results shed light on the importance of creating a favorable store atmosphere to enhance consumer perception and drive positive purchasing behaviors. The implications of this study offer valuable insights for practitioners seeking to optimize store environments and boost customer satisfaction and loyalty within the global noodle industry. Highlights: Store atmosphere significantly impacts purchasing decisions. Noodle consumers' perceptions of store atmosphere influence their purchasing behavior. Understanding the influence of store atmosphere can help optimize marketing strategies. Keywords: Store atmosphere, Purchasing decisions, Noodle consumers, Influence, Insights.